2008
DOI: 10.1149/1.2981893
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Liquid Water Distribution in Porous Transport Layers

Abstract: The local saturation in porous transport layers (PTL) has been determined using synchrotron-based x-ray micro-tomography. The water distribution inside the porous structure could be resolved on the scale of the pores. After phase segmentation of the image data, the measurement of the liquid saturation as function of the through plane coordinate of the PTL and the capillary pressure was possible. For verification, first experiments with complete cells are also shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 7 publications
2
28
0
Order By: Relevance
“…From the channel/GDL interface, the saturation level drops gradually to zero half way through the GDL. Similar water distribution trend in the GDL during imbibition was also observed by Büchi [8]. Fig.…”
Section: Resultssupporting
confidence: 85%
“…From the channel/GDL interface, the saturation level drops gradually to zero half way through the GDL. Similar water distribution trend in the GDL during imbibition was also observed by Büchi [8]. Fig.…”
Section: Resultssupporting
confidence: 85%
“…Synchrotron X-ray radiography offers high spatial and temporal resolutions (less than 10 μm and less than 10 s, respectively) [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Though X-ray photons are not as sensitive as a neutron beam to the presence of liquid water, Chevalier et al [29] demonstrated that synchrotron X-ray radiography can achieve similar accuracy to neutron radiography with a high level of precision.…”
Section: Visualizations Of Liquid Water Saturationmentioning
confidence: 99%
“…Over the last several years, there has been a significant effort in characterizing morphology and water distribution within the pores of the GDL by using X-ray computed tomography (CT) [25][26][27][28][29][30][31][32].…”
Section: Kim and Menchmentioning
confidence: 99%